An investigation on frequency characteristics of wireless power transfer systems with relay resonators. Issue 6 (6th November 2017) - Zhou, Jiali; Zhang, Bo; Qiu, Dongyuan
Abstract : Purpose: This paper aims to analyze the frequency characteristics of wireless power transfer (WPT) systems with relay resonators in terms of the power delivered to the load and system efficiency. Based on the analytical results, system parameters can be optimized to achieve maximum power transfer and higher system efficiency. Design/methodology/approach: Based on Kirchhoff's voltage law equations, WPT systems with relay resonators are described by the coupled linear second-order differential equations. Splitting frequencies are estimated by using the matrix theory. In addition, critical coupling conditions are demonstrated based on discriminant analysis. Findings: It was found that multi-maximum values exist for the power delivered to the load and total system efficiency owing to multiple eigenfrequencies of the system. Also, frequency conditions of maximum power transfer and system efficiency, as well as their critical coupling conditions, were quantitatively estimated. Research limitations/implications: During our analytical process, we assume that quality factors of resonators in the system are high and the crossing coupling between resonators is negligible. Originality/value: In previous works, the exact analysis of frequency characteristics is limited to WPT systems with two resonators. The appealing feature of this work lies in its ability to present a simplified analytical method with negligible approximation errors for WPT systems with relay resonators.